PCT testing in sepsis protocols - Valencia, Luke (Frontiers in Analytical Science, 2023)
Septicemia is a prominent disease with a mortality rate of over 20%, making it one of the most expensive illnesses for hospitals in the United States. Many cells throughout the body release procalcitonin (PCT) in response to severe bacterial infection. This literature review attempts to assess PCT testing as a potential addition to sepsis protocols and to identify recommendations when implementing PCT testing into sepsis workups. The incorporation of PCT testing could significantly reduce the financial burden, antibiotic usage, and mortality rates in sepsis cases.